ENT 530 Social Media Portfolio / Nur Izatul Amirah Khalilullah - Khalilullah, Nur Izatul Amirah (2019)
The business I have chosen is under health and beauty. The product is named as Raffaz Lip Scrub. Raffaz Lip Scrub is mainly about lip care product that have three flavours which are peppermint, lemon raspberry, and vanilla orange. The founder of this business is Nur lzatul. Amirah binti Khalillullah. The business address is No. 66, Lorong 4, Taman Raya Batu 40, 45200 Sabak Bernam, Selangor.